MONITORING PERTUMBUHAN FISIK BALITA UNTUK PENDETEKSIAN DINI STUNTING ANAK BERBASIS MOBILE - Rahayu, Ratna Rahmawati; Wulandari, Sekar; Wahyudi, Flagon Eka; Ramadhan, Muhammad Raffa (Jurnal Teknik Informasi dan Komputer (Tekinkom), 2025)
Stunting is a nutritional deficiency that results in impaired growth and development in children. In Indonesia, the prevalence of stunting has emerged as a pressing public health concern. The government has implemented a series of measures to address the issue of stunting. However, the prevalence of stunting in 2023 showed only a marginal decrease of 0.1% compared to the previous year. The determination of an individual's nutritional status is contingent upon the utilization of the Standard Antropometry Table, which is predicated on the calculation of Z-Score limits. These limits are determined by the age, weight, and height of the subject. In order to prevent stunting, it is essential to conduct a timely assessment of the nutritional status of children. The objective of this study is to facilitate the detection of nutritional status using a system that incorporates a nutritional status assessment for children. This system is designed to detect stunting using a mobile interface, with a user interface based on XML and Android Studio. The developed system is capable of displaying the nutritional status of the child, the presence of stunting, and the child's growth patterns.